Eleni - Gage, Nicholas 1939- (Random House, 1983)
"A savage war, a mother's love, and a son's revenge : a personal story."
Keywords: Gage, Nicholas; Gatzoyiannis, Eleni; Gatzogiannēs, Eleni -- ca. ca. 1906-1948; Geschichte; Journalists -- United States -- Biography; Griechischer Bürgerkrieg; Griechenland; USA; Greece -- Biography; Greece -- History -- Civil War, 1944-1949; Biografie -- 1940-1948